Mapping Historical Archaeology and Industrial Heritage: The Historical Spatial Data Infrastructure. Issue 1 (21st October 2021) - Trepal, Dan; Lafreniere, Don; Stone, Timothy
While a vibrant and growing research literature exists on the value of GIS to archaeology in general, the application of geospatial digital data to the subfield of historical archaeology is less well developed, especially in North America. This is particularly true for the era of industrialization, where the archaeological record is accompanied by a comparatively rich historical record. Historical and industrial archaeology are fundamentally bound up in the interplay between material and historical data, and it is in enhancing the dialogue between these two evidentiary bodies that interdisciplinary geospatial approaches are most fruitful to these subdisciplines. Drawing on recent discussions in digital archaeology and Historical GIS (HGIS), which has a robust history in the social sciences and humanities, we present an approach to modelling, visualizing, and analyzing longitudinal physical and social environment data for historical and industrial archaeology: a Historical Spatial Data Infrastructure (HSDI). Our HSDI, which is data-rich and highly flexible in scale, is especially well-adapted to facilitating this dialogue within archaeological research, as well as having important applications to heritage management and public engagement, as demonstrated in our case study.